Constructing noble-metal-free Z-scheme photocatalytic overall water splitting systems using MoS2 nanosheet modified CdS as a H2 evolution photocatalyst. Issue 40 (29th September 2017) - Yuan, Yong-Jun; Chen, Daqin; Yang, Shuhui; Yang, Ling-Xia; Wang, Jing-Jing; Cao, Dapeng; Tu, Wenguang; Yu, Zhen-Tao; Zou, Zhi-Gang
Abstract : A noble-metal-free Z-scheme system was constructed for photocatalytic overall splitting. Abstract : Photocatalytic overall splitting of H2 O into H2 and O2 using Z-scheme systems is a promising method for solar hydrogen generation. Most currently designed Z-scheme systems are usually based on precious metal cocatalyst modified semiconductor photocatalysts, thus exploiting noble-metal-free cocatalysts to replace precious metals is of huge interest. Herein, a noble-metal-free Z-scheme photocatalytic overall water splitting system was constructed by using MoS2 /CdS as the H2 evolution photocatalyst, Co3 O4 /BiVO4 as the oxygen evolution photocatalyst and a [Co(bpy)3 ] 3+ /[Co(bpy)3 ] 2+ redox couple as an electron mediator under visible light irradiation. It is found that the H2 and O2 evolution rates are approximate to an ideal ratio of 2 : 1, and the highest H2 and O2 evolution rates under visible light irradiation ( λ > 420 nm) are found to be 14.5 and 7.1 μmol h −1, respectively, with an excellent stability exceeding 12 h. The apparent quantum yield reaches up to 1.04% at wavelength λ = 420 nm even without any noble metal. The excellent stability and efficiency of this designed Z-scheme system in neutral water demonstrate its potential use for solar hydrogen generation. This work provides a noble-metal-free approach to construct the Z-scheme photocatalytic overall water splitting system.